Illocutionary Act Found on Character Arthur Fleck’s in Joker Movie - Theresia Cicik Sophia; Luki Saptiko; Siti Musarokah (SALEE: Study of Applied Linguistics and English Education, 2021)
This study is focused on the illocutionary acts found on Arthur Fleck’s dialogues in Joker (2019) movie. The objectives of this study are (1) to find out the types of illocutionary acts used by the character Arthur in Joker movie and (2) to find out the dominant types of illocutionary acts used by the character Arthur in Joker movie and what that means. To reach those objectives of study, the writers use Searle (2002) theory to conduct the study. There are five types of illocutionary acts according to Searle (2002). They are assertive, directive, commisive, expressive, and declarative. This study used qualitative design because it is framed in terms of using words instead of numbers. The result of data finding shows that there were 52 utterances done by Arthur Fleck indicates as illocutionary acts. The illocutionary types found are assertive, directive, commissive, expressive, and declarative. There are 8 utterances categorized as assertives type, 27 utterances categorized as directives type, 4 utterances categorized as commissive type, 9 utterances categorized as expressives type, and 4 utterances categorized as declaratives type. Directive type is the dominant type found in Arthur’s utterances. Keywords: Pragmatic, Illocutionary Acts, Joker (2019) Movie.